New advances in the creation of nanostructured materials - Grobert, N; Hare, J; Hsu, W; Kroto, H; Terrones, M; Walton, D; Zhu, Y (1999)
New advances have been made in the creation of nanostructured materials by pyrolytic and electrolytic methods. These experiments have shown that a wide range of nanostructures can be made using imaginative approaches.